DEVELOPMENT AND EVALUATION OF ORAL SUSTAINED-RELEASE RANITIDINE DELIVERY SYSTEM BASED ON BACTERIAL NANOCELLULOSE MATERIAL PRODUCED BY KOMAGATAEIBACTER XYLINUS - NGUYEN, THANH XUAN; PHAM, MUNG VAN; CAO, CUONG BA (International Journal of Applied Pharmaceutics, 2020)
Objective: The short biological half-life (2-3 h) and low bioavailability (50 %) of ranitidine (RAN) following oral administration favor the development of a controlled release system. This study was aimed to develop and in vitro evaluate oral sustained-release RAN delivery system based on the bacterial nanocellulose material (BNM) produced by Komagataeibacter xylinus (K. xylinus) from selected culture media. Methods: BNMs are biosynthesized by K. xylinus in the standard medium (SM) and coconut water (CW). RAN was loaded in BNMs by the absorption method. The structural and physicochemical properties of BNMs and BNMs-RAN were evaluated via swelling behavior, FTIR, and FESEM techniques. Moreover, the effect of BNMs on RAN release profile and release kinetics was analyzed and evaluated. Results: The amount of loaded RAN or entrapment efficacy for BNM-CW is higher than for BNM-SM. The BNM-SM-RAN and BNM-CW-RAN exhibited a decreased initial burst release system followed by a prolonged RAN release up to 24 h in relation to the commercial tablets containing RAN. The RAN release from these formulations was found higher in the SGF medium than that of in SIF medium. RAN released from these formulations was found to follow the Korsmeyer-Peppas model and diﬀusion sustained drug release mechanism. The sustained release of RAN from BNM-SM-RAN was slower than for RAN from BNM-CW-RAN, but the mechanism of sustained RAN release was the same. Conclusion: Oral sustained-release RAN delivery system based on BNMs was successfully prepared and evaluated for various in vitro parameters. The biopolymers like BNM-SM and BNM-CW could be utilized to develop oral sustained RAN release dosage form.